American utopia - Kalman, Maira 1949- (Bloomsbury Publishing, 2020)
"A joyful collaboration between old friends David Byrne and Maira Kalman, American Utopia offers readers an antidote to cynicism, bursting with pathos, humanism, and hope--featuring his words and lyrics brought to life with more than 150 of her colorful paintings. The text is drawn from David Byrne's American Utopia, which has become a hit Broadway show and is soon to be a documentary from Spike Lee. The four-color artwork, by Maira Kalman, which she created for the Broadway show's curtain, is composed of small moments, expressions, gestures, and interactions that together offer a portrait of daily life and coexistence"--Provided by publisher
"This dear book was born from the words & art of the hit musical 'American Utopia'"--Back cover
Keywords: Kalman, Maira -- 1949-; Byrne, David -- 1952- -- American utopia -- Zusammenstellung; Zeichnung; Byrne, David / 1952- / American utopia / In art; Kalman, Maira / Themes, motives; Kalman, Maira; Themes, motives; Art; Artists' books; Bildband